Preparation and in-vitro characterization of Risperidone-cyclodextrin inclusion complexes as a potential injectable product - Shukla D.; Chakraborty S.; Singh S.; Mishra B. (My University, 2025)
Background and the purpose of the study: This investigation deals with risperidone cyclodextrin (CD) complexation for parenteral administration to improve its aqueous solubility which would be beneficial over immediate and sustained release formulations available in market especially for agitated and non-cooperative psychotic patients. Methods: The phase solubility study of the drug with β-CD, hydroxypropyl (HP)-β-CD and γ-CD was conducted and CDs with higher stability constants were selected for complexation. The complexes of Risperidone with β-CD and HP-β-CD were prepared by precipitation and vacuum drying methods, respectively. Fourier transform-infrared, X-ray diffraction and differential scanning calorimetry techniques were used for characterization of complexes. Drug precipitation study of complex's solution in water for injection and 100 ml of 0.1 M pH 7.4 phosphate buffer saline and stability study in accelerated condition were also carried out. Results: The stability constants of the CD were in the following order: β-CD (341.953±11.87 M-1) > HP-β-CD (170.817± 5.93 M-1) > γ-CD (93.716 ± 3.25 M-1). CDs with high stability constants were selected to prepare the drug CD complex. The complexation efficiencies of â-CD and HP-β-CD were 95.23 ± 2.27% and 97.59 ±1.97%, respectively. Both types of CDs exhibited complexation at 1:2 molar stoichiometric ratio. The drug precipitation study indicated complete solubility (100% drug dissolution) without a trace of precipitate within 5 mins. The complexes were found to be stable for a period of 3 months under accelerated stability conditions. Major conclusion: Stable complexes of risperidone were successfully formulated using both β-CD and HP-β-CD by simple and highly efficient methods of complexation for parenteral administration.